FTIR and XRD studies on some archaeological artifacts from Bohn, India - Manoharan, K.Veeramuthu, R. Venkatachalapathy, A. Loganathan, C. (Recent Research in Science and Technology, 2009)
Spectroscopic studies have been performed on archaeological pottery samples from Bhon in Maharashtra. The clay mineral type and its structural deformation due to firing have been studied from their Fourier Transform Infrared (FTIR) spectra. The maximum firing temperature attained during baking, firing conditions (open/reduced atmosphere) and iron mineral phase changes are well established. X-ray diffraction (XRD) studies on archaeological artifacts pave the way to identify the minerals.